Critical Review: Professional Development Programs to Face Open Educational Resources in Indonesia - Rian Fitriansyah; Lisfatul Fatinah; Muhammad Syahril (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
Information and Communication Technology (ICT) in education has become an important issue in education reform in many countries such as Hong Kong, Singapore, the United States, and the United Kingdom. Education reform is needed to give skill set of the 21st century to students. Indonesian government has begun implementing ICT in education since 2002 marked by the establishment of the Indonesian Telematics Coordinating Team (TKTI). Although the development of ICT is still far away compared to Hong Kong and Singapore, ICT development is on the right track. In 2013, Indonesia began to initiate Open Educational Resources (OER) and teacher training on ICT. Open educational resources are digitized materials that can be freely accessed by those who want to teach, learn, or research. The OER initiatives have many challenges ahead, one of them is the development of the OER community involving all teachers in Indonesia. The gap in education quality between islands in Indonesia is added with the differences of education infrastructure and education resources. Therefore, Indonesia must create personalized professional development program based on the need of each island. The Indonesia government could initiate the OER consortium to unite all teachers to build a knowledge society. The methods of creating a professional development program could be deducted from the U.S. which has many districts and gap in education quality between states. The purpose of this paper is to develop a professional development program in creating the OER community in Indonesia. This paper tries to investigate what kind of professional development that has been set in, analyze the problems that would likely to occur, and give some solutions.